IMMUNE PROTECTION OF SALVINIA MOLESTA D.S. MITCHELL IN FRESHWATER CRAB OZIOTELPHUSA SENEX SENEX BACTERIALLY CHALLENGED WITH AEROMONAS HYDROPHILA - Tg, Nithya; J, Jayanthi; Mg, Ragunathan; D, Devakumar (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Â  Â Objective: This is aimed to study the immune protection parameters of freshwater weed Salvinia molesta in bacterially challenged freshwater crab Oziotelphusa senex senex. Methods: In this present study, ethanolic extract of freshwater weed S. molesta was tested for its ability to induce immunity in bacterial challenged freshwater crab O. senex senex. Male and female crabs were challenged with Aeromonas hydrophila in relevant concentrations. The treated groups were allowed to withstand for 96 hrs. After relevant incubation time, the hemolymph of the treated crabs was subjected for various hematological, biochemical, and immunological assays. Results: Total hemocyte count increased on infection at 96 hrs, whereas significantly reduced on treatment with S. molesta at 96 hrs. All the three cell types of differential hemocytes showed significant positive changes on treatment. Levels of prophenoloxidase decreased significantly on infection and showed a significant increase in treated groups at 96 hrs of treatment. Conclusion: The present study elucidated the medicinal and pharmaceutical role of S. molesta weed which is been subjected to eradication in the recent days. Thus, the plant source can be utilized as an immunomodulatory agent and a better alternative to treat aquatic diseases.